(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The purpose of this study was to examine the influence of job insecurity, workload, and work-family conflict on work stress among female workers in Central Jakarta. Drawing on the Job Demands–Resources (JD-R) theory, this study explains that work stress arises when work-related demands exceed employees' available resources to cope with them. A quantitative method with causal relationship analysis was applied. Data were collected through questionnaires distributed to 140 participants selected through purposive sampling, consisting of female workers in Central Jakarta who were married and/or had families and had worked for at least one year. All measurement indicators were adapted from established previous studies and assessed using a five-point Likert scale. The collected data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The findings indicate that job insecurity, workload, and work-family conflict have positive and significant effects on work stress, with workload exerting the strongest influence among the three independent variables. These results support the Job Demands–Resources (JD-R) theory, suggesting that excessive work demands and employment uncertainty contribute to higher levels of work stress among female workers. This study provides both theoretical and practical contributions by extending the application of the JD-R framework in the context of female workers in Central Jakarta and offering empirical evidence that can assist organizations in developing strategies to improve employee well-being through better workload management, enhanced employment security, and policies that support work-family balance. However, this study is limited to female workers in Central Jakarta and only examines three independent variables. Therefore, future research is recommended to involve more diverse respondents from different regions and occupational sectors while incorporating additional variables or mediation and moderation models to obtain a more comprehensive understanding of work stress.